A literature review of optimization problems for reconfigurable manufacturing systems. Issue 13 (2019) - Brahimi, Nadjib; Dolgui, Alexandre; Gurevsky, Evgeny; Yelles-Chaouche, Abdelkrim R.
Abstract: This paper is a literature review focusing on optimization problems for reconfigurable manufacturing systems (RMS). The literature is classified in two manners. In the first classification, different optimization problems rising in RMS are provided and discussed. The second one presents solution approaches used to solve these problems. This work is intended to help scientists identify potential research areas in the domain of optimization for RMS.